[tex]a)\\(x^{2}-4)(x+3)x = 0\\\\x(x+2)(x-2)(x+3) = 0\\\\x = 0 \ \vee \ x+2 = 0 \ \vee \ x - 2 = 0 \ \vee \ x+3 = 0\\\\x = 0 \ \vee \ x = -2 \ \vee \ x = 2 \ \vee \ x = -3\\\\x \in\{-3, -2, 0, 2\}[/tex]
[tex]b)\\(x^{2}+4)(x^{2}-4) = 0\\\\(x^{2}+4)(x+2)(x-2) = 0\\\\x^{2}+4 = 0 \ \vee \ x+2 = 0 \ \vee \ x - 2 = 0\\\\x^{2}\neq -4\\\\x = -2 \ \vee \ x = 2\\\\x \in \{-2, 2\}[/tex]
[tex]c)\\5x^{2}(x-1)(x^{2}-1) = 0 \ \ /:5\\\\x^{2}(x-1)(x+1)(x-1) = 0\\\\x^{2} = 0 \ \vee \ x-1 = 0 \ \vee \ x+1 = 0 \ \vee \ x - 1 = 0\\\\x = 0 \ \vee \ x = 1 \ \vee \ x = -1 \ \vee \ x = 1\\\\x \in \{-1, 0, 1\}[/tex]